405 nm ultraviolet photodetector based on tungsten disulphide thin film grown by drop casting method - Ahmad, Harith; Rashid, Haroon (Taylor & Francis, 2019)
In this work, a tungsten disulphide or WS2 based heterojunction photodetector device is fabricated on top of Si substrate by simple drop casting. Raman shifts are observed at 350.16 and 419.36 cm−1, confirming the successful growth of the WS2 and the non-stoichiometric WS2 layers which are verified by energy-dispersive X-ray (EDX) spectroscopy. The device is characterized for its optoelectronic properties in the ultraviolet (UV) range of 405 nm. Current–voltage (I–V) measurement is performed to obtain the I–V curves of the photodiode under laser illumination at 30.219, 56.335, 80.457, 106.998 and 129.28 mW.cm−2. The photocurrent is found to be highly dependent on the laser power. The fabricated device has a high responsivity of 145.52 mA/W and a high detectivity of 1.248 × 1011 Jones for an incident laser power density of 129.28 mW.cm−2. These observed results are promising and indicate the viability of the proposed design for optoelectronic applications. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.